2019
DOI: 10.1038/s41467-019-09455-9
|View full text |Cite
|
Sign up to set email alerts
|

A gut microbiome signature for cirrhosis due to nonalcoholic fatty liver disease

Abstract: The presence of cirrhosis in nonalcoholic-fatty-liver-disease (NAFLD) is the most important predictor of liver-related mortality. Limited data exist concerning the diagnostic accuracy of gut-microbiome-derived signatures for detecting NAFLD-cirrhosis. Here we report 16S gut-microbiome compositions of 203 uniquely well-characterized participants from a prospective twin and family cohort, including 98 probands encompassing the entire spectrum of NAFLD and 105 of their first-degree relatives, assessed by advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
237
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(276 citation statements)
references
References 62 publications
(74 reference statements)
17
237
1
10
Order By: Relevance
“…In an initial study determining metabolites and composition, there was a clear difference between patients with and without cirrhosis. 85 In the first metagenomics study, Proteobacteria increased with worsening fibrosis in NAFLD and at the species level, Eubacterium rectale, Ruminococcus obeum CAG: 39, were the most abundant organisms in mild/moderate NAFLD while B. vulgatus and E. coli were the most abundant in advanced fibrosis. 85 This was subsequently extended to a larger population, albeit from the same centre, with 30 factors (including 27 bacteria and remaining metabolites) as differentiators.…”
Section: Translating Our Current Microbial Knowledge Into Practice Inmentioning
confidence: 99%
“…In an initial study determining metabolites and composition, there was a clear difference between patients with and without cirrhosis. 85 In the first metagenomics study, Proteobacteria increased with worsening fibrosis in NAFLD and at the species level, Eubacterium rectale, Ruminococcus obeum CAG: 39, were the most abundant organisms in mild/moderate NAFLD while B. vulgatus and E. coli were the most abundant in advanced fibrosis. 85 This was subsequently extended to a larger population, albeit from the same centre, with 30 factors (including 27 bacteria and remaining metabolites) as differentiators.…”
Section: Translating Our Current Microbial Knowledge Into Practice Inmentioning
confidence: 99%
“…There have been recent advances in using bacterial taxonomy to predict NAFLD disease states 55 ; however, evidence of functional redundancy between different microbial taxa linked to proinflammatory pathways suggests that genes, rather than taxa, are likely to prove better biomarkers for the identification and characterization of NAFLD. Accordingly, we found that genus abundance measurements were inadequate for predicting disease using CART.…”
Section: Proinflammatory Pathways Associated With Disease Severitymentioning
confidence: 99%
“…NAFLD patients have a higher prevalence of dysbiosis with increased Bacteroides , Escherichia , and Ruminococcus , and decreased Prevotella bacteria in those with advanced forms of the disease, indicating an association between Gram­negative bacteria and progression of liver fibrosis . Additionally, fecal‐microbiome‐derived signatures associated with fibrotic NASH and NAFLD‐related cirrhosis have been described . Also, a significant association between NAFLD and SIBO has been established .…”
Section: Introductionmentioning
confidence: 97%